PERENCANAAN KEBUTUHAN BAHAN BAKU PADA PROSES PRODUKSI TAS DENGAN MENGGUNAKAN METODE MATERIAL REQUIREMENT PLANNING (MRP) - Muchammad Bagas Efendi; Andhika Mayasari (INVANTRI (Inovasi Dan Pengelolaan Industri), 2021)
UD. Elindo Jaya is a home industry engaged in making bags. This home industry manages raw materials into finished goods. Inventory is important for the home industry. Availability of raw materials in the right amount and time is a support for the smooth production process and can avoid shortages and excess of raw materials that can affect costs incurred. The problem that is formulated is how many raw materials for each order and when the components of these raw materials must be available in the warehouse in the right amount and time. The purpose of this study is to determine the amount of raw materials per order so that effectiveness can be achieved and to know the amount and time that must be available for the smooth running of the production process. Material requirement planning (MRP) is a method for knowing the planning of the production process and the raw material requirements for each component and determining the lead time for orders. From the data processing analysis carried out based on the MRP method, the raw material for producing 1000 bags requires 2.2 rolls of varing material on the 3rd day, 2000 sewing threads on the 4th day, 5.5 miniso material on the 3rd day, 2,2 zipper rollers on the 4th day, and 100 M of the rante accessories on the 4th day.